Rocks in the Stream: An Exploration of Knowledge Flow Inhibitors and Modulators within Organizations - Kasten, Joseph (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This study analyzes the flow of knowledge within firms at the individual level. Managers participate in semi-structured interviews. Content analysis identifies factors that obstruct or modulate the flow of knowledge such as knowledge filtering and packaging. These must be understood in order to create more effective knowledge flow within organizations. Cette étude analyse la circulation des connaissances dans les organisations au niveau individuel. Les gestionnaires participent à des entrevues semi-structurées. Une analyse du contenu identifie les facteurs qui entravent ou modulent la circulation des connaissances, comme le filtrage et l’intégration des connaissances. Ces facteurs doivent être compris de manière à créer une circulation des connaissances plus efficace dans les organisations.